2006
DOI: 10.1186/1479-5868-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundSelf-report recall questionnaires are commonly used to measure physical activity, energy expenditure and time use in children and adolescents. However, self-report questionnaires show low to moderate validity, mainly due to inaccuracies in recalling activity in terms of duration and intensity. Aside from recall errors, inaccuracies in estimating energy expenditure from self-report questionnaires are compounded by a lack of data on the energy cost of everyday activities in children and adolescents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(95 citation statements)
references
References 35 publications
2
92
0
1
Order By: Relevance
“…The MARCA has same-day test-retest reliability of r =0.84-0.92 for major outcome variables, and validity with reference to accelerometry of r = 0.45 for physical activity level (PAL) [48]. Children were asked to recall their activities for the two previous days (48 hours).…”
Section: Methodsmentioning
confidence: 99%
“…The MARCA has same-day test-retest reliability of r =0.84-0.92 for major outcome variables, and validity with reference to accelerometry of r = 0.45 for physical activity level (PAL) [48]. Children were asked to recall their activities for the two previous days (48 hours).…”
Section: Methodsmentioning
confidence: 99%
“…The daily energy intake used in this analysis is the average of the two 24 h recalls. Participants aged 9-16 years used the validated Multimedia Activity Recall for Children and Adolescents (MARCA) [17] to provide two consecutive days of physical activity and 'use of time' recall data at both the CAPI and CATI. Data from the MARCA were used to estimate average daily duration of moderate to vigorous physical activity (MVPA), total screen time (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…When the data collection in the present study took place in late 2007, such technologies were largely unavailable. Therefore the data do not reflect the widespread penetration of mobile technologies in the lives of today's adolescents (Rideout, Foehr, & Roberts, 2010). Furthermore, the diary instrument did not distinguish between Computer/Internet use for gaming or social networking, two activities reported in more recent literature as significantly gendered.…”
Section: Limitations and Contributionmentioning
confidence: 98%
“…In their study of the school-day time use of 6,024 Australian adolescents (mean age 13 years), collected using the computer administered Multimedia Activity Recall for Children and Adolescents (MARCA) (Ridley, Olds, & Hill, 2006), they found that at all ages, boys spent significantly more time in physical activity, organised sport, watching TV and playing videogames, while girls spent more time shopping, doing chores, playing with pets and using their phones. Supporting Zuzanek's (2005) assertion of the narrowing of the digital divide, no differences in computer time were found in the Australian study.…”
Section: Gendermentioning
confidence: 99%